EFEKTIFITAS SOCIAL MEDIA MARKETING DAN PERSONAL SELLING MELALUI BRAND AWARENESS TERHADAP KEPUTUSAN MENDAFTAR KULIAH DI FEB UNISSULA - Khoerul Anam; Wahyu Setiawan; Marno Nugroho (Universitas Duta Bangsa Surakarta, 2025)
This study examines the influence of Social Media Marketing and Personal Selling on Enrollment Decisions with Brand Awareness as a mediating variable among FEB UNISSULA students. A quantitative approach with PLS-SEM was applied to data from 120 respondents. The results show that Social Media Marketing significantly affects both Brand Awareness and Enrollment Decisions, while Personal Selling only affects Brand Awareness. Brand Awareness does not directly influence enrollment decisions and does not mediate the relationship between the marketing strategies. These findings highlight the key role of social media in higher education promotion.